Global Research Trends and Knowledge Structure of Interdialytic Weight Gain in Hemodialysis: A Bibliometric Analysis Study (2016–2025) - Ginsa Sabella Elmorisna Sivanda; Arlina Dewi (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Purpose: This study aims to analyze global research trends on interdialytic weight gain (IDWG) in patients undergoing haemodialysis and to map the intellectual structure, publication patterns, and emerging research themes within the field. Design/Methodology/Approach: A bibliometric analysis with a descriptive quantitative approach was conducted using the Scopus database. Bibliographic data were retrieved on 19 January 2026 using keywords related to “interdialytic weight gain” and “hemodialysis”. A total of 170 English-language journal articles published between 2016 and 2025 met the inclusion criteria. Data were analyzed using the Bibliometrix package in RStudio and visualized using VOSviewer to examine publication performance, collaboration networks, keyword co-occurrence, and thematic evolution. Findings: The dataset comprised 170 articles published in 81 sources and authored by 1,049 researchers. The annual publication growth rate was 6.17%, with an average of 16.47 citations per document. Collaboration analysis revealed a high level of scientific cooperation, with an average of seven authors per article and an international co-authorship rate of 24.12%. Keyword co-occurrence and thematic mapping identified haemodialysis, interdialytic weight gain, and fluid management as the dominant research themes. Overlay and density visualizations indicated an increasing research interest in behavioral and psychosocial topics, including self-efficacy, adherence, and patient self-management. However, these themes remain less prominent than physiological and clinical research topics. Originality/Value: This study provides a comprehensive bibliometric overview of the global IDWG research landscape and highlights emerging thematic directions. The findings identify behavioral and psychosocial dimensions as developing but relatively underexplored areas, offering potential directions for future research in haemodialysis-related fluid management. Keywords: Bibliometric Analysis, Interdialytic Weight Gain, Haemodialysis, Self-Efficacy, Adherence to Fluid Restriction.